Hydrophilic coating as well as preparation method and application thereof
By applying a hydrophilic coating composed of a bonding layer and a lubricating layer on the guide wire and catheter, the problem of insufficient lubricity and firmness of the hydrophilic coating in the prior art is solved, and the guide wire and catheter are realized in the blood vessel. Stable and efficient lubrication reduces the risk of blood vessel damage and coagulation response.
Patent Information
- Application Number
- CN202510012083.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-02-11
AI Technical Summary
In the prior art, the lubricity and firmness of the hydrophilic coatings are insufficient, resulting in astringent astringent when the guidewire and catheter move within the blood vessel, increasing the risk of damage to blood cells and blood vessel walls, and possibly triggering a coagulation reaction.
A hydrophilic coating consisting of a bonding layer and a lubricating layer is adopted, which consists of a prepolymer, a first crosslinking agent, a first photoinitiator and a first solvent, and the lubricating layer is composed of a hydrophilic compound and a second crosslinking agent. , a stabilizer, a second photoinitiator and a second solvent, and the two layers are stably cross-linked by ultraviolet light irradiation to improve the firmness and lubricity of the coating.
The long-term stability and efficient lubrication effect of the hydrophilic coating are achieved, which reduces the damage to the blood vessels by the guidewire and catheter, avoids the coagulation reaction, and improves the convenience of operation during use.
Smart Images

Figure CN119405912A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical materials, and in particular to a hydrophilic coating and a preparation method and application thereof. Background Art
[0002] In vascular interventional treatment, interventional guidewires and catheters are key devices for introducing and delivering instruments to the lesion site, and the outer layers of guidewires and catheters are basically made of polymer materials such as polyurethane (PU), thermoplastic polyurethane (TPU), polyetheramide (Pebax), etc. Most of these materials are hydrophobic, and their surface friction coefficients are high. When the guidewire or catheter enters and exits the blood vessel and moves in the blood vessel, its hydrophobic surface will cause the product to become astringent when used, affecting the delivery function of the device. In severe cases, it will cause damage to blood cells and blood vessel walls, interfere with blood flow, and then cause coagulation reaction.
[0003] Coating the surface of these polymer materials with a hydrophilic coating can effectively reduce the surface friction coefficient, making it easier to operate. In addition, the product can reduce damage to the blood vessels when moving within the blood vessels and effectively avoid coagulation reactions.
[0004] During actual use, the guidewire and catheter need to be adjusted many times to be accurately positioned. Hydrophilic coatings with poor firmness are prone to fall off during the adjustment process, which will not only increase the friction coefficient and make pushing difficult, but the detached hydrophilic coating may also form blood clots in the blood vessels. Therefore, the lubricity and firmness of the hydrophilic coating have always been the key and difficulty in the research and development of hydrophilic coating technology.
[0005] Currently, most hydrophilic coatings cannot guarantee the long-term stability of the product during use, and the preparation method is relatively complicated, and the coating process is time-consuming and labor-intensive. Summary of the invention
[0006] The purpose of the present invention is to provide a hydrophilic coating and a preparation method and application thereof in view of the defects in the prior art. The hydrophilic coating has good lubricity and firmness.
[0007] To achieve the above object, in a first aspect, the present invention provides a hydrophilic coating, the hydrophilic coating comprising a bonding layer and a lubricating layer; The bonding layer is used to bond with the surface of the lubricated object, and the components of the bonding layer include: 5%-12% of prepolymer, 0.3%-2.5% of first crosslinking agent, 0.05%-0.8% of first photoinitiator and 85%-94% of first solvent; The lubricating layer covers the bonding layer, and the components of the lubricating layer include: 2%-7% of a hydrophilic compound, 1%-5% of a second cross-linking agent, 0%-0.3% of a stabilizer, 0.05%-0.8% of a second photoinitiator and 88%-96% of a second solvent; wherein the first cross-linking agent is the same as the second cross-linking agent.
[0008] Preferably, the prepolymer has a molecular weight of 1000-50000 and includes one or more of polyester acrylate, unsaturated polyester, polyurethane acrylate, epoxy acrylate, polyether acrylate, polyene thiol system, and water-based acrylate.
[0009] Preferably, the molecular weight of the first cross-linking agent is 100-2000, including: one or more of polyethylene glycol diacrylate, diethylenetriamine, and ethylene glycol dimethacrylate; the molecular weight of the second cross-linking agent is 100-2000, including: one or more of polyethylene glycol diacrylate, diethylenetriamine, and ethylene glycol dimethacrylate.
[0010] Preferably, the first photoinitiator includes: one or more of Irgacure 127, Irgacure 1173, Irgacure 2959, benzophenone, Irgacure 2022, and (2,4,6-trimethylbenzoyl)diphenylphosphine oxide TPO; the second photoinitiator includes: one or more of Irgacure 127, Irgacure 1173, Irgacure 2959, benzophenone, Irgacure 2022, and (2,4,6-trimethylbenzoyl)diphenylphosphine oxide TPO.
[0011] Preferably, the molecular weight of the hydrophilic compound is not less than 200,000, and includes one or more of hyaluronic acid, polyvinyl pyrrolidone, polyacrylamide, polyvinyl alcohol, and polyacrylate.
[0012] Preferably, the molecular weight of the stabilizer is 600-2000, including one or more of polyoxyethylene sorbitan monooleate, polyethylene oxide sorbitan monostearate, and polyoxyethylene sorbitan palmitate.
[0013] Preferably, the first solvent is one or more of water, methanol and ethanol; the second solvent is one or more of water, methanol and ethanol.
[0014] In a second aspect, the present invention provides a method for preparing a solution of a hydrophilic coating as described in any one of the first aspects above, the preparation method comprising: Under light-proof conditions, adding the prepolymer to a first solvent for ultrasonic dispersion, then adding a first cross-linking agent, and stirring at room temperature for a first period of time to obtain a first mixed solution; Under light-proof conditions, dissolving a first photoinitiator in the first solvent, adding the first photoinitiator into the first mixed solution, and stirring at room temperature for a second period of time to obtain a binding layer solution; Under light-shielding conditions, adding a hydrophilic compound to the second solvent, stirring at room temperature for a third period of time, then adding a second cross-linking agent that is the same as the first cross-linking agent and mixing evenly, and then adding a stabilizer and mixing evenly to obtain a second mixed solution; Under light-proof conditions, dissolving the second photoinitiator in the second solvent, adding it into the second mixed solution, and stirring it at room temperature for a fourth period of time to obtain a lubricating layer solution, thereby obtaining a hydrophilic coating solution including a bonding layer solution and a lubricating layer solution.
[0015] Preferably, the ultrasonic dispersion time is 10 min-90 min, the first time length is 1 hour-3 hours, the second time length is 0.5 hour-2 hours, the third time length is 1 hour-5 hours, and the fourth time length is 0.5 hour-2 hours.
[0016] In a third aspect, the present invention provides a use of a hydrophilic coating as described in any one of the first aspects above, wherein the hydrophilic coating can be applied to lubricated objects made of polyurethane PU, thermoplastic polyurethane TPU, polyetheramide Pebax, nylon PA, polyvinyl chloride PVC and silicone materials, as well as the surface of irregular catheters, the surface of guide wires, and the surface of catheters with an inner diameter of 0.012 inches to 0.096 inches.
[0017] The hydrophilic coating provided by the embodiment of the present invention includes a bonding layer and a lubricating layer, wherein the bonding layer is bonded to the surface of the lubricated object by polymerization of a prepolymer, thereby improving the firmness of the bonding between the hydrophilic coating and the lubricated object; the second cross-linking agent of the lubricating layer is the same as the first cross-linking agent, so that it can stably cross-link with the bonding layer, thereby ensuring the firmness of the bonding between the lubricating layer and the bonding layer; the presence of the hydrophilic compound makes the lubricating layer hydrophilic, so that when the lubricated object having the hydrophilic coating is used in a working environment, the hydrophilic coating can have a good lubricating effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 A flow chart of a method for preparing a solution of a hydrophilic coating provided in an embodiment of the present invention; Figure 2 This is a test diagram of the friction coefficient of the catheter provided in Example 1 of the present invention; Figure 3 A test diagram of the friction coefficient of the catheter provided in Example 2 of the present invention; Figure 4This is a test diagram of the friction coefficient of the catheter provided in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0021] An embodiment of the present invention provides a hydrophilic coating, which may specifically include a bonding layer and a lubricating layer, and the friction coefficient is not greater than 0.04.
[0022] The composition of the bonding layer may specifically include: 5%-12% prepolymer, 0.3%-2.5% first crosslinking agent, 0.05%-0.8% first photoinitiator and 85%-94% first solvent. Preferably, it includes: 7%-9% prepolymer, 0.5%-2.2% first crosslinking agent, 0.2%-0.5% first photoinitiator and 88%-91% first solvent.
[0023] The molecular weight of the prepolymer is 1000-50000, and may include one or more of polyester acrylate, unsaturated polyester, polyurethane acrylate, epoxy acrylate, polyether acrylate, polyene thiol system, and water-based acrylate.
[0024] The molecular weight of the first cross-linking agent is 100-2000, and may include one or more of polyethylene glycol diacrylate, diethylenetriamine, and ethylene glycol dimethacrylate.
[0025] The first photoinitiator may include one or more of Irgacure 127, Irgacure 1173, Irgacure 2959, benzophenone, Irgacure 2022, and (2,4,6-trimethylbenzoyl)diphenylphosphine oxide TPO.
[0026] The first solvent may be one or more of water, methanol, and ethanol.
[0027] The bonding layer serves as the bottom layer of the hydrophilic coating and is generally in contact with the surface of the object to be lubricated. When irradiated with ultraviolet light, the prepolymer can be polymerized under the action of the first photoinitiator and the first cross-linking agent to generate a sticky polymer, which adheres to the surface of the object to be lubricated, thereby improving the firmness of the connection between the hydrophilic coating and the object to be lubricated.
[0028] The composition of the lubricating layer specifically includes: 2%-7% of a hydrophilic compound, 1%-5% of a second crosslinking agent, 0%-0.3% of a stabilizer, 0.05%-0.8% of a second photoinitiator, and 88%-96% of a second solvent. Preferably, it includes: 4%-6% of a hydrophilic compound, 1%-4% of a second crosslinking agent, 0%-0.1% of a stabilizer, 0.1%-0.5% of a second photoinitiator, and 90%-95% of a second solvent.
[0029] The molecular weight of the hydrophilic compound is not less than 200000, and may include: one or more of hyaluronic acid, polyvinyl pyrrolidone, polyacrylamide, polyvinyl alcohol, and polyacrylate. The addition of the hydrophilic compound makes the lubricating layer hydrophilic.
[0030] The molecular weight of the second cross-linking agent is 100-2000, and may include: one or more of polyethylene glycol diacrylate, diethylenetriamine, and ethylene glycol dimethacrylate. The second cross-linking agent is the same as the first cross-linking agent.
[0031] The molecular weight of the stabilizer is 600-2000, and may include one or more of polyoxyethylene sorbitan monooleate, polyethylene oxide sorbitan monostearate, and polyoxyethylene sorbitan palmitate.
[0032] The second photoinitiator may include one or more of Irgacure 127, Irgacure 1173, Irgacure 2959, benzophenone, Irgacure 2022, and (2,4,6-trimethylbenzoyl)diphenylphosphine oxide TPO.
[0033] The second solvent may be one or more of water, methanol, and ethanol.
[0034] The lubricating layer mainly plays a lubricating role due to its hydrophilicity and is generally covered on the bonding layer as a surface layer. The second cross-linking agent is the same as the first cross-linking agent, so that the lubricating layer and the bonding layer can be stably cross-linked under ultraviolet light, ensuring the firmness of the hydrophilic coating.
[0035] In summary, the hydrophilic coating provided by the embodiment of the present invention includes a binding layer and a lubricating layer, wherein the binding layer is bonded to the surface of the lubricated object by polymerization of a prepolymer, thereby improving the firmness of the bonding between the hydrophilic coating and the lubricated object; the second cross-linking agent of the lubricating layer is the same as the first cross-linking agent, so that it can be stably cross-linked with the binding layer, thereby ensuring the firmness of the bonding between the lubricating layer and the binding layer; the presence of the hydrophilic compound makes the lubricating layer hydrophilic, so that when the lubricated object having the hydrophilic coating is used in a working environment, the hydrophilic coating can have a good lubricating effect.
[0036] The present invention also provides a method for preparing the above-mentioned hydrophilic coating solution, which mainly comprises the following steps: Figure 1 The steps shown in: It should be noted that the materials of the hydrophilic coating involved in the following steps are all the materials mentioned above, which will not be described again here.
[0037] Step 110, adding the prepolymer to a first solvent for ultrasonic dispersion under light-shielding conditions, then adding a first cross-linking agent, and stirring at room temperature for a first period of time to obtain a first mixed solution; Specifically, the ultrasonic dispersion time can be 10 min-90 min, preferably 30 min, and the first time can be 1 hour-3 hours, preferably 2 hours. Stirring can be achieved by mechanical stirring or magnetic stirring.
[0038] Step 120, dissolving the first photoinitiator in the first solvent under light-proof conditions, adding the first photoinitiator to the first mixed solution, and stirring at room temperature for a second period of time to obtain a binding layer solution; Specifically, the second time length can be 0.5 hours to 2 hours, preferably 1 hour. The first photoinitiator is dissolved in the first solvent alone, and then mixed with the first mixed solution, so that the dissolution time of the first photoinitiator can be reduced, thereby saving the preparation time of the solution of the entire hydrophilic coating. The binding layer solution needs to be kept away from light. When the hydrophilic coating needs to be applied, the binding layer solution is first applied as a base liquid on the surface of the lubricated object, and the prepolymer is polymerized and bonded to the surface of the lubricated object, thereby improving the firmness of the hydrophilic coating.
[0039] Step 130, adding a hydrophilic compound to the second solvent under light-shielding conditions, stirring at room temperature for a third period of time, then adding a second cross-linking agent that is the same as the first cross-linking agent and mixing, and then adding a stabilizer and mixing to obtain a second mixed solution; Specifically, the third duration may be 1 hour to 5 hours, preferably 3 hours.
[0040] Step 140, dissolving the second photoinitiator in the second solvent under light-proof conditions, adding the second photoinitiator into the second mixed solution, and stirring at room temperature for a fourth period of time to obtain a lubricating layer solution, thereby obtaining a hydrophilic coating solution including a bonding layer solution and a lubricating layer solution.
[0041] Specifically, the fourth time length can be 0.5 hours to 2 hours, preferably 1 hour. The lubricating layer solution needs to be kept away from light. When the hydrophilic coating needs to be applied, the lubricating layer solution is applied to the surface of the binding layer as a surface liquid, and the second cross-linking agent is cross-linked with the first cross-linking agent, further improving the firmness of the hydrophilic coating. The coating time is shortened. The hydrophilic compound makes the hydrophilic coating hydrophilic, and when it comes into contact with a hydrophilic substance, it has a good lubricating effect.
[0042] The method for preparing a hydrophilic coating solution provided in an embodiment of the present invention obtains a hydrophilic coating solution by separately preparing a binding layer solution and a lubricating layer solution. When it is needed, the binding layer solution is first applied as a base liquid on the surface of the object to be lubricated, and the prepolymer is polymerized and bonded to the surface of the object to be lubricated, thereby improving the firmness of the hydrophilic coating. The lubricating layer solution is applied as a surface liquid on the surface of the binding layer, and the second cross-linking agent is cross-linked with the first cross-linking agent, further improving the firmness of the hydrophilic coating. The hydrophilic compound makes the hydrophilic coating hydrophilic, and when it comes into contact with a hydrophilic substance, it has a good lubricating effect. The preparation method can be implemented only at room temperature and in the dark, and the operation is simple and fast, and the coating time is greatly shortened, thereby improving the coating efficiency.
[0043] The hydrophilic coating provided by the embodiment of the present invention can be applied to lubricated objects made of polyurethane (PU), thermoplastic polyurethane (TPU), polyetheramide (Pebax), nylon (PA), polyvinyl chloride (PVC) and silicone materials. It can also be applied to the surface of irregular catheters such as balloon catheters, the surface of guide wires, and the surface of catheters with an inner diameter of 0.012-0.096 inches.
[0044] The following uses the lubricated object as a catheter as an example to illustrate the use of the hydrophilic coating.
[0045] First, the distal end of the catheter is sealed with a silicone plug or a heat shrink tube.
[0046] Secondly, immerse the catheter in the bonding layer solution at a speed of 10mm / s-30mm / s for 2s-20s, then pull the catheter at a speed of 5mm / s-15mm / s. After the catheter is completely pulled, irradiate it with ultraviolet light for 20s-150s, so that the prepolymer is cross-linked under the action of ultraviolet light and adheres to the surface of the catheter to obtain a catheter with a bonding layer.
[0047] Then, the catheter bonded with the bonding layer is immersed in the lubricating layer solution at a speed of 10mm / s-30mm / s, soaked for 2s-20s, and then pulled at a speed of 5mm / s-15mm / s. After the catheter is completely pulled, it is irradiated with ultraviolet light for 50s-300s to obtain a catheter coated with a hydrophilic coating.
[0048] In order to better understand the technical solution provided by the present invention, the following uses a number of specific examples to illustrate the specific process of preparing a hydrophilic coating using the method provided by the above embodiment of the present invention, as well as the properties of the prepared hydrophilic coating.
[0049] Example 1 In the first step, under light-proof conditions, 25 g of polyurethane acrylate was added to 300 mL of ethanol, and ultrasonically dispersed for 30 minutes. Then, 5 g of polyethylene glycol diacrylate (molecular weight 308) was slowly added thereto, and magnetic stirring was performed for 2 hours to obtain a first mixed solution.
[0050] In the second step, 1 g of Irgacure 2959 was dissolved in 60 mL of ethanol under light-proof conditions, and added to the first mixed solution, and magnetically stirred for 1 hour to obtain a binding layer solution, which was then stored in the dark. The binding layer solution included 7.94% polyurethane acrylate, 1.59% polyethylene glycol diacrylate, 0.32% Irgacure 2959, and 90.16% ethanol.
[0051] The third step is to magnetically stir 300 mL of ethanol at room temperature under light-proof conditions, then slowly add 15 g of polyvinyl pyrrolidone (molecular weight 360,000) thereto, stir at room temperature for 3 hours, then add 7 g of polyethylene glycol diacrylate thereto, continue stirring for 0.5 hour, and then dissolve 0.5 g of polyoxyethylene sorbitan monooleate therein to obtain a second mixed solution.
[0052] Step 4: Dissolve 0.4 g of Irgacure 2959 in 60 mL of ethanol under light-proof conditions, add the mixture to the second mixed solution, stir magnetically for 1 hour, obtain a lubricating layer solution, and store it in a dark place. The lubricating layer solution includes 4.89% polyvinyl pyrrolidone, 2.28% polyethylene glycol diacrylate, 0.18% polyoxyethylene sorbitan monooleate, 0.13% Irgacure 2959, and 92.54% ethanol.
[0053] Afterwards, a catheter having an inner diameter of 0.072 inches and a surface comprising TPU and Pebax was coated with the hydrophilic coating solution prepared above, and the friction coefficient was tested.
[0054] First, the distal end of the catheter was sealed with a silicone plug, and then its outer surface was wiped with ethanol.
[0055] Secondly, the catheter was immersed in the bonding layer solution at a speed of 15 mm / s for 5 seconds, and then the catheter was pulled up at a speed of 10 mm / s. After the catheter was completely pulled up, it was irradiated with ultraviolet light for 50 seconds, so that the polyurethane acrylate was cross-linked under the action of ultraviolet light and bonded to the surface of the catheter, thereby obtaining a catheter with a bonding layer.
[0056] Then, the catheter bonded with the bonding layer was immersed in the lubricating layer solution at a speed of 15 mm / s for 5 seconds, and then pulled up at a speed of 10 mm / s. After the catheter was completely pulled up, it was irradiated with ultraviolet light for 60 seconds to obtain a catheter coated with a hydrophilic coating.
[0057] Finally, a fully automatic friction tester was used for inspection. The catheter coated with the hydrophilic coating was immersed in water for 30 seconds, the clamping force was 300g, the speed was 10mm / s, and the catheter was tested 40 times.
[0058] Example 2 In the first step, under light-proof conditions, 25 g of polyurethane acrylate was added to 300 mL of ethanol, and ultrasonically dispersed for 30 minutes. Then, 4 g of polyethylene glycol diacrylate (molecular weight 700) was slowly added thereto, and magnetic stirring was performed for 2 hours to obtain a first mixed solution.
[0059] In the second step, 0.8 g of Irgacure 2959 was dissolved in 60 mL of ethanol under light-proof conditions, and added to the first mixed solution, and magnetically stirred for 1 hour to obtain a binding layer solution, which was then stored in the dark. The binding layer solution included 7.97% polyurethane acrylate, 1.28% polyethylene glycol diacrylate, 0.25% Irgacure 2959, and 90.5% ethanol.
[0060] The third step is to magnetically stir 300 mL of ethanol at room temperature under light-proof conditions, then slowly add 15 g of polyvinyl pyrrolidone (molecular weight 360,000) thereto, stir at room temperature for 3 hours, then add 5 g of polyethylene glycol diacrylate thereto, and continue stirring for 0.5 hours to obtain a second mixed solution.
[0061] Step 4: Dissolve 0.3 g of Irgacure 2959 in 60 mL of ethanol under light-proof conditions, add the mixture to the second mixed solution, stir magnetically for 1 hour, obtain a lubricating layer solution, and store it in a dark place. The lubricating layer solution includes 4.93% polyvinyl pyrrolidone, 1.64% polyethylene glycol diacrylate, 0.1% Irgacure 2959, and 93.33% ethanol.
[0062] The testing process is the same as in Example 1.
[0063] Example 3 In the first step, 15.17 g of polyester acrylate was added to 300 mL of methanol under light-shielding conditions, and ultrasonically dispersed for 10 min. Then, 1.52 g of diethylenetriamine (molecular weight 103) was slowly added thereto, and magnetically stirred for 1 hour to obtain a first mixed solution.
[0064] In the second step, 1.52 g of Irgacure 127 was dissolved in 60 mL of methanol under light-proof conditions, and added to the first mixed solution, and magnetically stirred for 0.5 hours to obtain a binding layer solution, which was then stored in the dark. The binding layer solution included 5% polyester acrylate, 0.5% diethylenetriamine, 0.5% Irgacure 127, and 94% methanol.
[0065] The third step is to subject 300 mL of ethanol to magnetic stirring at room temperature under light-proof conditions, and then slowly add 5.92 g of hyaluronic acid (molecular weight 1,000,000) thereto, stir at room temperature for 1 hour, and then add 2.96 g of diethylenetriamine thereto, continue stirring for 0.5 hour, and then dissolve 0.59 g of polyethylene oxide sorbitan monostearate therein to obtain a second mixed solution.
[0066] Step 4: Dissolve 2.37 g of Irgacure 2022 in 60 mL of ethanol under light-proof conditions, add the mixture to the second mixed solution, stir under magnetic force for 0.5 hours, obtain a lubricating layer solution, and store it under light-proof conditions. The lubricating layer solution includes 2% hyaluronic acid, 1% diethylenetriamine, 0.2% polyethylene oxide sorbitan monostearate, 0.8% Irgacure 2022, and 96% ethanol.
[0067] Example 4 In the first step, 50.82 g of epoxy acrylate was added to 300 mL of water under light-proof conditions, and ultrasonically dispersed for 90 min. Then, 9.32 g of polyethylene glycol diacrylate (molecular weight 2000) was slowly added thereto, and magnetically stirred for 3 hours to obtain a first mixed solution.
[0068] In the second step, 3.39 g of Irgacure 1173 was dissolved in 60 mL of water under light-proof conditions, and added to the first mixed solution, and magnetically stirred for 2 hours to obtain a binding layer solution, which was then stored in the dark. The binding layer solution included 12% epoxy acrylate, 2.2% polyethylene glycol diacrylate, 0.8% Irgacure 1173, and 85% water.
[0069] The third step is to magnetically stir 300 mL of water at room temperature under light-proof conditions, then slowly add 28.64 g of polyacrylamide (molecular weight 6,000,000) thereto, stir at room temperature for 5 hours, then add 18.41 g of polyethylene glycol diacrylate thereto, and continue stirring for 0.5 hours to obtain a second mixed solution.
[0070] Step 4: Dissolve 2.05 g of Irgacure 2959 in 60 mL of water under light-proof conditions, add the mixture to the second mixed solution, stir magnetically for 2 hours, obtain a lubricating layer solution, and store it in a dark place. The lubricating layer solution includes 7% polyacrylamide, 4.5% polyethylene glycol diacrylate, 0.5% Irgacure 2959, and 88% water.
[0071] Example 5 In the first step, under light-proof conditions, 22.02 g of polyether acrylate was added to 300 mL of ethanol, and ultrasonically dispersed for 60 min. Then, 7.86 g of ethylene glycol dimethacrylate (molecular weight 198) was slowly added thereto, and magnetic stirring was performed for 2.5 hours to obtain a first mixed solution.
[0072] In the second step, 0.63 g of TPO was dissolved in 60 mL of ethanol under light-proof conditions, and added to the first mixed solution, and magnetically stirred for 0.8 hours to obtain a binding layer solution, which was then stored in the dark. The binding layer solution included 7% polyether acrylate, 2.5% ethylene glycol dimethacrylate, 0.2% TPO, and 90.3% ethanol.
[0073] The third step is to subject 300 mL of ethanol to magnetic stirring at room temperature under light-proof conditions, and then slowly add 12.56 g of polyacrylate (molecular weight 500,000) thereto, stir at room temperature for 4 hours, and then add 1.49 g of ethylene glycol dimethacrylate thereto, continue stirring for 0.5 hour, and then dissolve 0.75 g of polyoxyethylene sorbitan palmitate therein to obtain a second mixed solution.
[0074] Step 4: Dissolve 0.15 g of TPO in 60 mL of ethanol under light-proof conditions, add the mixture to the second mixed solution, stir magnetically for 0.8 hours, obtain a lubricating layer solution, and store it in a dark place. The lubricating layer solution includes 4.2% polyacrylate, 0.5% ethylene glycol dimethacrylate, 0.25% polyoxyethylene sorbitan palmitate, 0.05% TPO, and 95% ethanol.
[0075] Example 6 In the first step, 28.31 g of aqueous acrylate was added to 300 mL of methanol under light-proof conditions, and ultrasonically dispersed for 40 min. Then, 0.94 g of polyethylene glycol diacrylate (molecular weight 308) was slowly added thereto, and magnetic stirring was performed for 2 hours to obtain a first mixed solution.
[0076] In the second step, 0.16 g of benzophenone was dissolved in 60 mL of methanol under light-proof conditions, and the mixture was added to the first mixed solution, and magnetic stirring was performed for 1 hour to obtain a binding layer solution, which was then stored in the dark. The binding layer solution included 9% aqueous acrylate, 0.3% polyethylene glycol diacrylate, 0.05% benzophenone, and 90.65% methanol.
[0077] The third step is to magnetically stir 300 mL of water at room temperature under light-proof conditions, then slowly add 24 g of polyvinyl alcohol (molecular weight 200,000) thereto, stir at room temperature for 3 hours, then add 14.8 g of polyethylene glycol diacrylate thereto, continue stirring for 0.5 hours, and then dissolve 0.4 g of polyethylene oxide sorbitol monostearate therein to obtain a second mixed solution.
[0078] Step 4: Dissolve 0.8 g of benzophenone in 60 mL of water under light-proof conditions, add the solution to the second mixed solution, stir the mixture under magnetic force for 1 hour, obtain a lubricating layer solution, and store the solution in the dark. The lubricating layer solution includes 6% polyvinyl alcohol, 3.7% polyethylene glycol diacrylate, 0.1% polyethylene oxide sorbitol monostearate, 0.2% benzophenone, and 90% water.
[0079] Comparative Example 1 The test was conducted using a fully automatic friction tester. A catheter with an inner diameter of 0.072 inches and a surface comprising TPU and Pebax without a hydrophilic coating was immersed in water for 30 seconds and tested with a clamping force of 300 g and a speed of 10 mm / s.
[0080] like Figure 2 and 3 As shown in , the maximum friction coefficient of the catheter in Example 1 and Example 2 of the present invention does not exceed 0.04, and the maximum friction force is calculated to be no more than 12g. After 40 tests, the friction coefficient value is stable and does not increase, indicating that the hydrophilic coating does not fall off after 40 frictions and its firmness is very good.
[0081] like Figure 4 As shown in , the maximum friction coefficient of the catheter in Comparative Example 1 is greater than 1.3 before 40 tests, indicating that its surface lubricity is poor.
[0082] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A hydrophilic coating, characterized in that: The hydrophilic coating comprises a bonding layer and a lubricating layer; The bonding layer is used to bond with the surface of the lubricated object, and the components of the bonding layer include: 5%-12% of prepolymer, 0.3%-2.5% of first crosslinking agent, 0.05%-0.8% of first photoinitiator and 85%-94% of first solvent; The lubricating layer covers the bonding layer, and the components of the lubricating layer include: 2%-7% of a hydrophilic compound, 1%-5% of a second cross-linking agent, 0%-0.3% of a stabilizer, 0.05%-0.8% of a second photoinitiator and 88%-96% of a second solvent; wherein the first cross-linking agent is the same as the second cross-linking agent.
2. The hydrophilic coating according to claim 1, characterized in that: The prepolymer has a molecular weight of 1000-50000 and includes one or more of polyester acrylate, unsaturated polyester, polyurethane acrylate, epoxy acrylate, polyether acrylate, polyene thiol system, and water-based acrylate.
3. The hydrophilic coating according to claim 1, characterized in that: The molecular weight of the first cross-linking agent is 100-2000, including: one or more of polyethylene glycol diacrylate, diethylenetriamine, and ethylene glycol dimethacrylate; the molecular weight of the second cross-linking agent is 100-2000, including: one or more of polyethylene glycol diacrylate, diethylenetriamine, and ethylene glycol dimethacrylate.
4. The hydrophilic coating according to claim 1, characterized in that: The first photoinitiator includes: one or more of Irgacure 127, Irgacure 1173, Irgacure 2959, benzophenone, Irgacure 2022, and (2,4,6-trimethylbenzoyl)diphenylphosphine oxide TPO; the second photoinitiator includes: one or more of Irgacure 127, Irgacure 1173, Irgacure 2959, benzophenone, Irgacure 2022, and (2,4,6-trimethylbenzoyl)diphenylphosphine oxide TPO.
5. The hydrophilic coating according to claim 1, characterized in that: The molecular weight of the hydrophilic compound is not less than 200,000, and includes one or more of hyaluronic acid, polyvinyl pyrrolidone, polyacrylamide, polyvinyl alcohol, and polyacrylate.
6. The hydrophilic coating according to claim 1, characterized in that: The molecular weight of the stabilizer is 600-2000, and includes one or more of polyoxyethylene sorbitan monooleate, polyethylene oxide sorbitan monostearate, and polyoxyethylene sorbitan palmitate.
7. The hydrophilic coating according to claim 1, characterized in that: The first solvent is one or more of water, methanol and ethanol; the second solvent is one or more of water, methanol and ethanol.
8. A method for preparing a solution of a hydrophilic coating as claimed in any one of claims 1 to 7, characterized in that: The preparation method comprises: Under light-proof conditions, adding the prepolymer to a first solvent for ultrasonic dispersion, then adding a first cross-linking agent, and stirring at room temperature for a first period of time to obtain a first mixed solution; Under light-proof conditions, dissolving a first photoinitiator in the first solvent, adding the first photoinitiator into the first mixed solution, and stirring at room temperature for a second period of time to obtain a binding layer solution; Under light-shielding conditions, adding a hydrophilic compound to the second solvent, stirring at room temperature for a third period of time, then adding a second cross-linking agent that is the same as the first cross-linking agent and mixing evenly, and then adding a stabilizer and mixing evenly to obtain a second mixed solution; Under light-proof conditions, dissolving the second photoinitiator in the second solvent, adding it into the second mixed solution, and stirring it at room temperature for a fourth period of time to obtain a lubricating layer solution, thereby obtaining a hydrophilic coating solution including a bonding layer solution and a lubricating layer solution.
9. The preparation method according to claim 8, characterized in that: The ultrasonic dispersion time is 10 min-90 min, the first time length is 1 hour-3 hours, the second time length is 0.5 hour-2 hours, the third time length is 1 hour-5 hours, and the fourth time length is 0.5 hour-2 hours.
10. Use of the hydrophilic coating according to any one of claims 1 to 7, characterized in that: The hydrophilic coating can be applied to lubricated objects made of polyurethane PU, thermoplastic polyurethane TPU, polyether amide Pebax, nylon PA, polyvinyl chloride PVC and silicone materials, as well as the surface of irregular catheters, the surface of guide wires, and the surface of catheters with an inner diameter of 0.012 inches to 0.096 inches.
Citation Information
Patent Citations
Stabilized compositions containing alkaline labile drugs
CN101484142A
Silicone hydrogel lenses with nano-textured surfaces
CN103597378A
Hydrophilic super-lubricating coating applied to surfaces of medical apparatuses and preparation method of hydrophilic super-lubricating coating
CN107412883A
Super-hydrophilic coating for TPU coated guide wire and preparation method of super-hydrophilic coating
CN114748700A
Coating compositions, methods of making hydrophilic coatings on substrates, and medical devices comprising such coatings
CN115605522A